2015
DOI: 10.3390/nu7042193
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activity and Nutritional Status in Anorexia Nervosa: Effects of Weight Recovery

Abstract: Few studies are focused on the antioxidant status and its changes in anorexia nervosa (AN). Based on the hypothesis that renutrition improves that status, the aim was to determine the plasma antioxidant status and the antioxidant enzymes activity at the beginning of a personalized nutritional program (T0) and after recovering normal body mass index (BMI) (T1). The relationship between changes in BMI and biochemical parameters was determined. Nutritional intake, body composition, anthropometric, hematological a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 44 publications
1
15
1
Order By: Relevance
“…In a recent study, Oliveras-López reported in 25 participants with AN a significant increase in catalase activity (baseline: 25.04 ± 1.97 vs follow-up: 35.54 ± 2.60 μmol/min/mL; p < 0.01) as well as in total antioxidant capacity (from 1033.03 ± 34.38 to 1504.61 ± 99.73 μmol/L; p < 0.01). In this study, superoxide dismutase activity decreased significantly (baseline: 532.5 ± 93.4 vs follow-up: 281.4 ± 52.0 μmol/min/mL; p < 0.05), while glutathione peroxidase did not change significantly (Oliveras-López et al, 2015).…”
Section: Outcomes Summarised Descriptivelymentioning
confidence: 46%
See 1 more Smart Citation
“…In a recent study, Oliveras-López reported in 25 participants with AN a significant increase in catalase activity (baseline: 25.04 ± 1.97 vs follow-up: 35.54 ± 2.60 μmol/min/mL; p < 0.01) as well as in total antioxidant capacity (from 1033.03 ± 34.38 to 1504.61 ± 99.73 μmol/L; p < 0.01). In this study, superoxide dismutase activity decreased significantly (baseline: 532.5 ± 93.4 vs follow-up: 281.4 ± 52.0 μmol/min/mL; p < 0.05), while glutathione peroxidase did not change significantly (Oliveras-López et al, 2015).…”
Section: Outcomes Summarised Descriptivelymentioning
confidence: 46%
“…Six studies (Dostálová et al, 2010;Feillet et al, 2000;Haluzík et al, 1999;Oliveras-López et al, 2015;Russell et al, 1983;Umeki, 1988) involving 99 subjects demonstrated that weight gain was associated with a significant increase in the serum levels of the antioxidant albumin (SMD = 0.50, 95%CI = 0.18; 0.82, p = 0.002, I 2 = 16%; Fig. 1).…”
Section: Meta-analysis Of Oxidative Stress and Antioxidant Markers Inmentioning
confidence: 96%
“…A distinct TAS reduction in serum of AN patients was already reported [23,24]. This is also reflected in measurements of single antioxidant markers such as albumin, apolipoprotein B, and uric acid [23,[25][26][27][28].…”
Section: Discussionmentioning
confidence: 89%
“…This is also reflected in measurements of single antioxidant markers such as albumin, apolipoprotein B, and uric acid [23,[25][26][27][28]. Diminished uric acid level was also observed in extended period of time after realimentation [29].…”
Section: Discussionmentioning
confidence: 99%
“…In the refeeding status, the body shifts back instantaneously to carbohydrate metabolism [2][3][4]. Studies on anorexia nervosa patients and fish species showed that the starvation period has prooxidant effects due to both increased lipid peroxidation levels and the reduced level of antioxidant defenses [5][6][7][8]. Capability of refeeding in anorexia nervosa patients for reducing the oxidative stress or increasing the levels of antioxidant markers is unknown.…”
Section: Introductionmentioning
confidence: 99%